PENGUATAN KETERAMPILAN OLAHAN HASIL PERIKANAN UNTUK PEMBERDAYAAN MASYARAKAT PESISIR DESA TIHENGO, GORONTALO UTARA - Rachman, Agus Bahar; Mulyati, Yenni (Universitas Negeri Gorontalo, 2025)
Tihengo Village in Ponelo Kepulauan District, North Gorontalo Regency, is a coastal region with substantial fisheries resources. Despite this potential, the community exhibits limited fish processing capabilities, resulting in the sale of most catches in their raw form and generating minimal economic returns. The current community service initiative aimed to enhance participants' knowledge and skills in developing diversified, value-added fishery products. The program utilised a participatory methodology, including socialisation, technical training, practical exercises, and ongoing mentoring. Thirty-five participants, comprising fishermen, women, and youth from the village, were involved in the study. The intervention resulted in measurable gains in nutritional knowledge, sanitation and hygiene awareness, and technical proficiency in producing fish fillets, surimi, nuggets, and fish jelly. Nuggets and surimi were identified as the most favoured products due to their convenience and commercial viability, while fish jelly was recognised for its potential for product innovation. Overall, the program enhanced local food security, facilitated the establishment of small-scale fish-based enterprises, and aligned with national objectives to increase fish consumption.